PROBLEMATIKA BUDAYA MEMBACA DI IDONESIA - Jessy Ayu Angelia; Usiono Usiono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this research is to find out the problems of reading culture in Indonesia. This research method uses the Library study method.b Data collection is done by searching for sources and constructing from various sources such as books, journals and research that has been done. Reading culture is very important for Indonesian people so that people do not easily accept hoax news.